1942
DOI: 10.6028/jres.029.027
|View full text |Cite
|
Sign up to set email alerts
|

Further phase-equilibrium studies involving the potash compounds of portland cement

Abstract: The present research on the system K 20.23CaO.128iO, -CaO-5CaO.3Al,Ol is a part of the program designed to determine the manner in which 1(,0 affects the compound composition of portland cement clinker. Thermal and optical data are presented and a phase-equilibrium d iagram of this system has been constructed. The only compounds that were observed in the system under equilibrium cond itions are the components of the system and 3CaO.Ab03' The effect,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

1947
1947
1980
1980

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
1
5
0
2
Order By: Relevance
“…In agreement with th e work previously reported by Taylor [4], K 20.23CaO.12Si02 was found to react with CaS0 4 in an equimolar ratio upon h eating mixt.ures of t hose compounds in t he r egion of clinkering temperatures. The observed reaction products after quen ching th e mixture fr om 900° wer e i3-2CaO.Si02, ' Y-2CaO.Si02 and K 2S04. Preheated mixtures of K 20 .23CaO.12Si0 2 and CaS0 4 having molecular ratios K 20 jSOa, of 1, 2, and 3 (4 , 36, and 47, respectively, table 2) showed an endothermic transformation in the region of the K 2S04 m elting point during thermal analysis.…”
Section: Reaction Of K20 23caol2si02 With Cas04supporting
confidence: 90%
See 2 more Smart Citations
“…In agreement with th e work previously reported by Taylor [4], K 20.23CaO.12Si02 was found to react with CaS0 4 in an equimolar ratio upon h eating mixt.ures of t hose compounds in t he r egion of clinkering temperatures. The observed reaction products after quen ching th e mixture fr om 900° wer e i3-2CaO.Si02, ' Y-2CaO.Si02 and K 2S04. Preheated mixtures of K 20 .23CaO.12Si0 2 and CaS0 4 having molecular ratios K 20 jSOa, of 1, 2, and 3 (4 , 36, and 47, respectively, table 2) showed an endothermic transformation in the region of the K 2S04 m elting point during thermal analysis.…”
Section: Reaction Of K20 23caol2si02 With Cas04supporting
confidence: 90%
“…These equations, in the convenient weight per centage form , appear in table 4. The appl~cation of the equations in table 4 (B ) (for those mIxtures having R 2 0 j80 3 molecular ratios greater than l.0) requires the preliminary calculation of the value of K s the mole fraction of K 280 4 in the sulfate, for th~ mixture as outlined in table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that, under equilibrium cooling, the prismatic form was not observed in any case. Under more rapid cooling the prismatic form appeared in those compositions in which C3A wa one of the compounds anticipated from the phase diagram [41]. If the charge were quenehed from a temperature above that at which C3A was formed, the prismatic phase was not found .…”
Section: Prismatic Tricalcium Aluminatementioning
confidence: 96%
“…Se pudo comprobar claramente el sulfato potásico en el clinker. De este modo se confirmaron los resultados de Taylor [1]: el K2SO4 es estable en presencia de las fases del clínker. El sulfato sódico, por el contrario, influye en la formación de las fases alita, belita y aluminato con la misma tendencia que el carbonato sódico, aun cuando de manera decididamente menor, pues a la temperatura de sinterización sólo se puede disponer de una fracción del óxido de sodio para la formación de las fases del clínker.…”
Section: Influencia De Los Sulfatos Alcalinos Sobre Las Fases Del CLIunclassified